Symmetrical Peripheral Gangrene: Report of Three Cases - Héctor Acosta; Pau Forcada; Marta Bonjorn; Amer Mustafa; Paul Pilares; Jordi Colomina (Case Reports in Critical Care)
Symmetrical peripheral gangrene (SPG) is a rare clinical syndrome characterized by an acute onset of ischemic damage in two or more extremities without obstruction or vasculitis of supplying vessels. Body parts commonly affected include toes, hands, scrotum, and earlobes, increasing the risk of limb amputation and impairing the quality of life. The vascular injury mechanism is disseminated intravascular coagulation. SPG may manifest unpredictably in conditions associated with septic shock, low output states, vasospastic conditions, myeloproliferative disorders, or hyperviscosity syndrome. A review on the topic is presented based on a 3-case series of SPG that required amputation of fingers and toes after the administration of vasopressors in a septic shock context.